Monitoring mitochondrial function in peripheral T cells to assess immune status and graft health after kidney transplantation - Zhang, Erdi; Wan, Zhengli; Ma, Yuwen; Li, Yamei; Zhou, Qixiang; Cai, Bei; Li, Yi; Li, Feng; Ying, Binwu; Yan, Lin (Frontiers in Immunology, 2026)
IntroductionKidney transplantation is the preferred treatment for end-stage renal disease, but immune-mediated graft dysfunction remains a major barrier to long-term success. Conventional indicators such as serum creatinine and proteinuria are not immune-specific, and kidney biopsy is unsuitable for routine use. Mitochondrial function, a critical regulator of immune activation, may provide novel biomarkers for immune monitoring in transplantation.MethodsIn this study, the percentage of peripheral immune cells with low mitochondrial membrane potential (MMP-Low%) and mitochondrial mass (MM) were assessed in 30 kidney transplant recipients and 44 healthy controls. Of the 30 transplant recipients, 15 provided paired samples before transplantation and at one month after transplantation with preserved graft function, while the other 15 had impaired graft function. Flow cytometry was used to measure lymphocyte subsets and mitochondrial parameters, which were further evaluated across specific T cell populations.ResultsThe results showed that increased age correlated with lower MMP-Low% and higher MM. Patients with impaired graft function showed significantly reduced MMP-Low% and elevated MM, suggesting enhanced metabolic activation, while those with preserved graft function displayed increased MMP-Low% and decreased MM, reflecting a quiescent metabolic profile consistent with immunosuppression.DiscussionThese findings indicate that peripheral T cell mitochondrial metrics may serve as sensitive, dynamic, and non-invasive biomarkers for post-transplant immune monitoring.